Cyber Sovereignty Gotong Royong, Indonesia’a Way of Dealing with the Challenges of Global Cyber Sovereignty - Nur Ro'is (Fakultas Hukum Universitas Lampung, 2022)
State sovereignty is born together with the independence of a country, as well as sovereignty in cyberspace. The state has sovereignty in cyberspace as in its territorial space so that it has jurisdictional authority, but in reality, there are unclear territorial boundaries in cyberspace. Indonesia today still has a dependence on foreign cyberinfrastructure, which causes a high level of cyber vulnerability and low cyber sovereignty resilience. Indonesia has local wisdom known as